Influence of Branch Incorporation into the Lamella Crystal on the Crystallization Behavior of Polyethylene with Precisely Spaced Branches (2013)
Depending on the degree of short chain branch (SCB) incorporation, the crystallization behavior and resultant crystalline structure drastically change in polyethylene with precisely spaced branches. In polyethylene with hexyl branches precisely spaced on every 21st carbon (HB21), only crystallization mediated by a transient hexagonal phase without incorporation of the SCB was observed. On the other hand, in polyethylene with ethyl branches precisely spaced on every 21st carbon (EB21), crystallization behavior was strongly dependent on the crystallization temperature. A thin lamella was formed through crystallization mediated by a hexagonal phase and no thickening occurred at 5–8 °C, while thickening of the transient hexagonal lamellae occurred at 10–15 °C, and one SCB seemed to be incorporated into a crystal stem. At 17 °C, no thickening of the hexagonal phase occurred and a hexagonal phase with sufficient lamella thickness was directly formed from the melt. At 21–28 °C, crystallization mediated by hexago.